The influence of game intervals on physical performance demands in elite futsal: insights from congested periods - Pereira, A.; Ribeiro, J. N.; Alcaraz, P.E.; Carrasco, R. H.; Travassos, B.; Freitas, T. T.; Spyrou, K. (Sports, 2025)
The aims of this study were to analyze (1) the external match demands during a congested period (CP) (i.e., three games in eight days) and (2) the differences among games with two- or three-day intervals in professional futsal players. Eleven elite male futsal players were monitored during 15 official matches. Wearable accelerometers were used to record player load (PL), accelerations (ACC), decelerations (DEC), and changes of direction (COD) at different intensities (e.g., high, medium, and low) using two approaches (e.g., absolute and relative per minute). A linear mixed model and effect sizes (ESs) were used to analyze differences between matches and days of interval. Considering the external match load during CP, non-significant differences were found for all the variables (p = 0.108-0.995; ES: 0.01-0.40). Comparing the interval days between games, players had significantly higher DECHI (p = 0.030; ES: 0.48), CODTOTAL (p = 0.028; ES: 0.33), CODMED (p = 0.024; ES: 0.40), and CODLOW (p = 0.038; ES: 0.31) following 3 days of interval between the games when compared with 2 days. However, when analyzed relative to effective time, non-significant differences were found. In summary, CPs seem to not affect the match external load, but players performed better in terms of DEC and COD following 3 days of interval when compared to 2 days when analyzed with absolute values.